Study of Sustainable Aspect in the Mbaru Niang Traditional House in Wae Rebo Village, East Nusa Tenggara - Princess Griffith Serafim; Christopher Daniel Suprapto; Agus Dwi Hariyanto (Advances in Civil Engineering and Sustainable Architecture, 2025)
This study examines the sustainability of the Mbaru Niang house in Wae Rebo Village, Indonesia, through a qualitative descriptive method. The analysis focuses on the spatial layout as well as supporting elements such as materials, climate responsiveness, and communal functions, using visual interpretation and thematic mapping based on environmental, social, and well-being dimensions. The findings reveal how the use of local materials, passive ventilation, communal spatial organization, and flexible design strategies reflect an integrated approach to sustainability. Mbaru Niang demonstrates how traditional architecture, grounded in ecological adaptation and cultural continuity, can inform contemporary sustainable design. While the study is limited by its reliance on secondary data and scope, it contributes to architectural discourse by emphasizing the value of traditional knowledge in creating resilient and context-sensitive built environments.